2016
DOI: 10.18869/acadpub.mlj.10.3.28
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ampc and Extended-Spectrum Beta-Lactamases in Clinical Isolates of Pseudomonas Aeruginosa from Patients with Cystic Fibrosis

Abstract: Background and Objectives: Pseudomonas aeruginosa is the most frequent opportunistic pathogen isolated from the sputum of patients with cystic fibrosis (CF). Resistance to β-lactam antibiotics may arise from over expression of the naturally occurring AmpC cephalosporinases or acquired extended-spectrum β-lactamases (ESBL). The aim of this study was to determine the antibiotic resistance profiles as well as the prevalence of ESBL and AmpC production in clinical isolates of P. aeruginosa from CF patients in Tehr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Among the fourth generation cephalosporins, such as cefepime, only less than 3.7% of studies reported a rate of resistance less than 10% [ 2 , 13 ], whereas in more than 20% of articles, the rate of resistance considered more than 90% [ 14 24 ]. More than 72% of studies revealed >50% level of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Among the fourth generation cephalosporins, such as cefepime, only less than 3.7% of studies reported a rate of resistance less than 10% [ 2 , 13 ], whereas in more than 20% of articles, the rate of resistance considered more than 90% [ 14 24 ]. More than 72% of studies revealed >50% level of resistance.…”
Section: Discussionmentioning
confidence: 99%